Interaction microenvironment - Pantoea agglomerans limits maize yield - Ruíz Juárez, Daniel; Azaola Espinosa, Alejandro; Esquivel Esquivel, Gilberto; Segundo Pedraza, Eva; Silva Rojas, Hilda Victoria (REVISTA TERRA LATINOAMERICANA, 2018)
Pantoea agglomerans has been reported as the cause of chlorotic streaks on maize leaves in the Central High Valleys of México (CVHM), but there are no current data of how the infection of this new pathogen in Mexico affects production and yield of the crop. To understand the development of the disease in the crop, two experiments with a split-plot design and three replications were established during spring-summer 2010 in different microenvironments: Ayapango and Temamatla. Three cultivars of maize (a tri-linear HS2 hybrid, the single-cross hybrid Triunfo and the native Cacahuacintle) were evaluated with three P. agglomerans isolates. In the three maize cultivars, chlorotic streaks appeared on new leaves; at the ripening stage, the symptoms were less perceptible. The average incidence of plants with chlorotic streaks was higher in the town of Temamatla than in Ayapango, and in both microenvironments, the average degree of severity was less than 40%. Isolate A was the most virulent (P < 0.0001) on the three cultivars evaluated. These results will provide the basis for effective management of the disease under environmental conditions similar to those evaluated in this research.